Panorama internacional das barreiras para inovação e sustentabilidade em universidades - Ávila, Lucas Veiga (2017)
The present study has as general objective to analyze the barriers that influence the process of innovation and sustainability in universities in an international context. Its intermediate objectives are: to investigate the barriers that influence the process of innovation and sustainability in universities, in the perspective of experts in an international context; analyze the innovation and sustainability barriers by continents of origin of the researched universities; to measure the barriers of innovation and sustainability, verifying their correlations and associations; to present recommendations through mechanisms for universities to overcome barriers, in search of innovation and sustainability. The study included two phases, the first of which was qualitative, carried out through questioning in an electronic form with the participation of 51 experts on the subject, in order to identify the barriers of innovation and sustainability in its university. The second phase, quantitative, was carried out by means of an electronic instrument with the participation of 283 university representatives, aiming to measure the degree of importance of the barriers in the process of development and implementation of innovation and sustainability. The analysis of the data, in the qualitative phase, was carried out by means of content analysis techniques with the support of Nvivo software and, for quantitative analysis, tests were carried out: descriptive factorial analysis, confirmatory factorial analysis and correlation analysis. As main results, it has been found that, while there has been evolution in the field of innovation and sustainability in universities around the world, there are still challenges to be overcome. Among these challenges is the need for universities to improve the integration of innovation and sustainability into curriculum and research and, most importantly, to seek holistic integration into their systems. It is recommended for universities, a set of mechanisms for the areas of institutional support; awareness, knowledge and culture; and infrastructure mechanisms, technologies and campus.